A Biased Coin Up-and-Down Sequential Allocation Trial to Determine the Optimum Programmed Intermittent Epidural Bolus Time Interval Between 5 mL Boluses of Bupivacaine 0.125% With Fentanyl 2 µg/mL. Issue 2 (June 2020) - Bittencourt, R.; Arzola, C.; Zakus, P.; Downey, K.; Ye, X.Y.; Carvalho, J.C.A.
Abstract : ( Can J Anesth . 2019 66:1075–1081) Programmed intermittent epidural bolus (PIEB) for labor analgesia has garnered a lot of attention and is the focus of ongoing research. PIEB when compared with continuous epidural infusion results in higher maternal satisfaction, reduced local anesthetic consumption, lower incidence of motor block, fewer unilateral blocks, and less breakthrough pain. The optimal epidural solution and PIEB settings for labor analgesia have yet to be decided. This study aimed to determine the effective PIEB time interval when using 5 mL boluses of bupivacaine 0.125% with fentanyl 2 mcg/mL.